Importance of Chakki (grinding stone) - Mumbai Archive Project Team (Jio Institute, 2024)
The chakki (grinding stone) is used in various ceremonies to represent strength, stability, and the enduring nature of marriage. During the wedding ceremonies, the bride and groom may place their feet or stand on the grinding stone, symbolizing their firm commitment to the vows they are making.